ANÁLISE DO PERFIL CLÍNICO, FUNCIONAL E DA QUALIDADE DE VIDA DE PACIENTES COM A SÍNDROME PÓS-COVID-19 - Audina Soares Rosa, Rafaela; Caldeira de Morais, Ana Carolina; Siqueira Diniz, Ingrid Iolanda; Braga Sclauser Pessoa, Isabela Maria (Sinapse Múltipla, 2022)